Pedagogy of Insurrection: From Resurrection to Revolution by Peter McLaren - English, Leona M. (Canadian Journal for the Study of Adult Education, 2016)
Book Review of: PEDAGOGY OF INSURRECTION: FROM RESURRECTION TO REVOLUTION Peter McLaren. Peter Lang Publishing, 2015, 465 pages.